2014
DOI: 10.1111/jphd.12078
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of complementary and alternative medicine (CAM) use among dental patients

Abstract: A large proportion of dental patients reported use of CAM therapies. While CAM therapies and those who use them are diverse, given their widespread use, they clearly have potential impacts on the oral health of the public. Knowledge of the characteristics of dental patients who use CAM therapies is a first step in developing a broader understanding how CAM therapies and associated beliefs may affect oral health and public health programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, studies in developed countries have reported a non-significant relationship between income and HM use but a significant relationship between higher level of education and HM use. 29 68 These variations may be due to interplay between factors such as respondent’s socioeconomic characteristics and peculiarities of the study environment. Hence, the findings in this study reflect such interplay where the middle-income class used more HM and a significant relationship between level of education and HM use.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in developed countries have reported a non-significant relationship between income and HM use but a significant relationship between higher level of education and HM use. 29 68 These variations may be due to interplay between factors such as respondent’s socioeconomic characteristics and peculiarities of the study environment. Hence, the findings in this study reflect such interplay where the middle-income class used more HM and a significant relationship between level of education and HM use.…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of dental patients have also been reported using of CAM therapies in the United States (Abebe et al, 2011; Spector et al, 2012; Kummet et al, 2015). Differ to medical school, however, it has not yet been widely spread the introduction of oriental medicine/CAM courses in an undergraduate education curriculum in US dental school (Spector et al, 2013., Madhan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This discipline includes a diverse set of approaches used for prevention and treatment of many diseases. 1 Several benefits of CAM have been proven, and it may be considered an effective modality for disease prevention, treatment of non-communicable diseases (NCDs), and for improving the quality of life (QOL) of individuals with chronic medical conditions. 2 Many patients who may not be satisfied with the outcomes of modern medicine, particularly those with chronic diseases, may be satisfied with the outcomes of CAM.…”
mentioning
confidence: 99%